The process of transformation of the Brazilian Army from the perception of Military Force officers - Moreira, Alexandre Santana; Schmitt, Valentina Gomes Haensel (Revista de Administração da UFSM, 2018)
The study aimed to analyze the perception of military officers, as students of the Army Command and Staff School (ECEME), about the current process of transformation of the Brazilian Army (EB). To reach the objectives, bibliographical and field researches were carried out, which were made by the quantitative analysis of the data collected. In the bibliographic research stage, the focus was on the understanding of the study problem, especially from the theory of organizational transformation. To understand the problem, the strategic, structural, technological, human, cultural and political dimensions were analyzed (MOTTA, 2001). The field research involved the collection of data through the application of a survey questionnaire, with five levels of response on the Likert scale, aiming to verify the perception of the individuals represented by the sample in relation to the process studied and the dimensions of analysis mentioned above. The sample was made up of officers, members of the student body of the Higher Studies course at ECEME (Brazilian Army Command and General Staff School), obtaining 148 (one hundred and forty-eight) valid questionnaires. The data treatment involved the use of Factor Analysis and Logistic Regression. The results of the study indicated that officials perceive the cultural, human and structural variables as having the greatest influence on the process of transformation in the company that it was studied. On the other hand, the strategic, technological and human variables were the most influential ones regarding the perception (positive or negative) about the process. At the end of the study are presented suggestions aimed at understanding the transformation process of EB (Brazilian Army), as well as propositions for managers about possibilities for their conduction and improvement of processes.